Rectifier Antenna (Rectenna) Microstrip Rectangular Patch Slot Horizontal On Television Signal Reception With Ultra High Frequency (UHF) Channeled - Nasrul Nasrul; Afrizal Yuhanef; Latifah Hanum (Politeknik Negeri Padang, 2024)
This study aims to design and test a Rectangular miscrostrip Rectifier antenna for television signal reception in the Ultra High Frequency (UHF) pathway. The research method includes designing antenna designs and designing Voltage Multiplier rectifier circuits. The antenna parameters measured include working frequency, Return Loss, Bandwidth, VSWR, Antenna Impedance, Polarization, and Gain. The results showed that the Return Loss value in the frequency range of 540-884 MHz had a value of ≤-10dB, with the lowest value of -26,868 dB at a frequency of 598 MHz in the simulation results. After fabrication, the Return Loss value in the frequency range of 632-785 MHz has a value of ≤-10dB, with the lowest value of -42,375 dB at a frequency of 668 MHz. or transmissions connected to it. The antenna impedance was 50.60Ω in the simulation results and 51.107 Ω in the measurement results.